RELIGIOUS AND POLITICS: THE CASE OF THE BULGARIAN ORTHODOX CHURCH - Serafimova, Marija 20./21. Jh. (Politikologija religije, 2007)
The Bulgarian society suff ers the consequences of the domination of the falsely accepted notion about ideology. The ideology was one the reasons for the pathology of the passed century, a taking shape civil society seemingly free of the power of the party-state. In the new situation the culture, state and religion are not the same as they have been. After the collapse of the communist rule and in the times of reappraisal of values, the Bulgarian Ortodox Church found itself in a situation of deep, acute and unprecedented crisis. The proces has many aspects - moral, political, canonical - which should always be differentiated.